Muslim Teachers: The Influence of Religiosity and Demographics on Learning Efficacy in Early Childhood Education - Rahayu, Agustina Dewi; Formen, Ali; Sugiyo Pranoto, Yuli Kurniawati (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Self-Efficacy plays an important role in supporting learning, as well as self-religiosity. As a Muslim teacher, it is necessary to have good self-efficacy and religiosity as a guide in teaching religious values to students. Teacher demographics here examine age and length of teaching. This study aims to examine whether there is an effect of religiosity, age, length of teaching on the efficacy of Muslim teachers in PAUD institutions. The research method used is quantitative research, with a sample of 323 Muslim teachers. The results of the study showed a significant influence between religiosity on the efficacy of Muslim teachers, where the higher the religiosity, the higher the efficacy of Muslim teachers. While age and length of teaching have no significant effect on the efficacy of Muslim teachers. The conclusion of this study is that the efficacy of Muslim teachers is influenced by the religiosity of teachers, but demographic backgrounds such as age and length of teaching do not affect the level of efficacy of Muslim teachers. The results of this survey still have research limitations, therefore researchers suggest further research on Muslim teacher efficacy by interviewing and completing individual demographic variables and social demographics.